2014
DOI: 10.3855/jidc.4405
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and risk factors for toxoplasmosis in large ruminants in northern Punjab, Pakistan

Abstract: Introduction: Toxoplasmosis is a widespread zoonosis that causes significant economic losses due to abortions and other developmental disabilities in livestock animals. The objectives of the current study were to determine the prevalence and associated risk factors of Toxoplasma gondii infection in cattle and buffaloes in northern parts of Punjab, Pakistan, where no such work previously existed. Methodology:Serum samples obtained from 400 cattle and 422 buffaloes present on different private and government-own… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
26
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 33 publications
8
26
2
1
Order By: Relevance
“…This was in disagreement with the results of Elfahal et al (2013) who found no significant relationship between antibody prevalence and breed. Ahmad et al (2015) found no significant breed-related difference with regard to seropositivity in goats, while it was significantly high in salt range sheep as compared to other breeds of sheep.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…This was in disagreement with the results of Elfahal et al (2013) who found no significant relationship between antibody prevalence and breed. Ahmad et al (2015) found no significant breed-related difference with regard to seropositivity in goats, while it was significantly high in salt range sheep as compared to other breeds of sheep.…”
Section: Discussionmentioning
confidence: 64%
“…Furthermore, age was an important factor for being seropositive as a measure of the cumulated life-time risk. Ahmad et al (2015) indicated that the likelihood of infection increased with age in sheep and goats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be emphasized that animal sanitation in Marajó Island is usually poor because of the lack of adequate animal management, and the physical characteristics of the region limit livestock productivity (BARBOSA, 2005). Ahmad and Qayyum (2014) observed that the number of animals positive for antibodies to T. gondii was significantly higher in farms with poor hygiene, and the presence of cats in the vicinity of the farm contributed to the spread of infection.…”
Section: Discussionmentioning
confidence: 96%
“…Results of this study revealed that 52.24% of cancer patients and 30.5% of the control group had chronic toxoplasmosis disease. 15.73% of cancer patients had acute Toxoplasma infection. However, 33.89% of toxoplasmosis patients had a cute infection.…”
mentioning
confidence: 99%